(581) Development of a dual economy تنمية الاقتصاد المزدوج - A. Qayum (معهد التخطيط القومي, 2026)
ملخص This study examines the process of economic development in developing countries through the analytical framework of a dual economy, characterized by the coexistence of two distinct sectors: a modern industrial sector operating according to the principles of contemporary economic organization and a traditional sector whose productive activities rely largely on customary practices and household-based enterprises. Building upon the pioneering contributions of development economists, particularly the work of Ranis and Fei, the study develops a mathematical model to analyze the dynamics of resource allocation, labor transfer, and capital accumulation between the two sectors. The research investigates the relationship between wages and the marginal productivity of labor, together with the roles of savings, investment, and capital formation in promoting economic growth. Special attention is given to the structural differences between the industrial and traditional sectors regarding labor absorption, productivity, and the generation of economic surplus. The study formulates a set of mathematical relationships describing the evolution of capital stock, employment levels, and output in each sector, while incorporating the effects of technological progress and improvements in productive efficiency. The findings suggest that sustained economic development depends on expanding productive investment, accelerating capital accumulation in the modern sector, and improving the efficiency of resource utilization. These processes facilitate the gradual transfer of surplus labor from low-productivity traditional activities to more productive modern employment opportunities. The analysis further demonstrates that technological advancement plays a decisive role in enhancing labor productivity and accelerating growth, while successful structural transformation requires a balanced interaction among population growth, technological change, savings behavior, and investment rates. The study concludes that the dual economy model provides a valuable theoretical framework for understanding the development challenges faced by emerging economies and offers important insights into the mechanisms through which economies evolve from traditional structures toward modern productive systems. Consequently, the model contributes to the formulation of effective development policies aimed at achieving sustainable economic growth, higher living standards, and comprehensive socioeconomic progress. تتناول هذه الدراسة قضية التنمية الاقتصادية في الدول النامية من خلال إطار نظري وتحليلي للاقتصاد المزدوج، وهو الاقتصاد الذي يتكون من قطاعين متباينين في الخصائص والبنية الإنتاجية؛ الأول قطاع حديث أو صناعي تتوافق فيه آليات الإنتاج والتوظيف مع مبادئ الاقتصاد الحديث، والثاني قطاع تقليدي يعتمد بدرجة كبيرة على الأساليب الموروثة والتنظيمات الأسرية منخفضة الإنتاجية. وتنطلق الدراسة من الأدبيات الرائدة في اقتصاد التنمية، ولاسيما أعمال رانيس وفاي، لتطوير نموذج رياضي يفسر ديناميكية انتقال الموارد وعوامل الإنتاج بين القطاعين ودورهما في عملية النمو الاقتصادي. وتركز الدراسة على تحليل العلاقة بين الأجور والإنتاجية الحدية للعمل، وافتراضات الادخار والاستثمار وتراكم رأس المال، مع إبراز الاختلافات الجوهرية بين القطاع الحديث والقطاع التقليدي في استيعاب العمالة وتوليد الفائض الاقتصادي. كما تقدم الدراسة مجموعة من المعادلات الرياضية التي تصف تطور رأس المال، ومستويات التشغيل، والإنتاج في كل قطاع، وتأثير التقدم التكنولوجي على معدلات النمو والكفاءة الإنتاجية. وتوضح النتائج أن التنمية الاقتصادية المستدامة تتطلب زيادة الاستثمار المنتج، وتحفيز تراكم رأس المال في القطاع الحديث، ورفع كفاءة استخدام الموارد، بما يسمح بامتصاص فائض العمالة من القطاع التقليدي وتحويله تدريجيًا إلى أنشطة أكثر إنتاجية. كما تؤكد الدراسة أن التقدم التقني يمثل عاملًا حاسمًا في تسريع النمو الاقتصادي وتحسين إنتاجية العمل، وأن نجاح عملية التحول الهيكلي يعتمد على التفاعل المتوازن بين النمو السكاني، والتغير التكنولوجي، ومعدلات الادخار والاستثمار. وتخلص الدراسة إلى أن نموذج الاقتصاد المزدوج يوفر إطارًا تحليليًا مهمًا لفهم مشكلات التنمية في الدول النامية، ويساعد في تفسير آليات التحول من الاقتصاد التقليدي إلى الاقتصاد الحديث، بما يدعم صياغة سياسات اقتصادية فعالة تستهدف تحقيق النمو المستدام ورفع مستويات المعيشة وتعزيز التنمية الشاملة.